TWELVE-DAY WAR FROM POINT OF VIEW OF STRATEGY - Vukovic, Nebojša (National interest, 2025)
The short-lived war between Israel and Iran in June 2025 was the culmination of decades of conflict between two states in the Middle East region. This war is multiple inspirable for research from different sciences or disciplines (military strategy, geopolitics, geostrategy, polemology, study of international relations, etc.) and can be analysed and viewed from a variety of conceptual and methodological angles. A deeper (scientific) understanding of this war requires not only its description and listing of the relevant events in it, but also its interpretation and explanation on the basis of already established and verified scientific paradigms. In this work, the Israeli-Iranian war will be investigated with the help of a significant paradigm from a (military) strategy. It is about the concept of two types of strategy – sequential and cumulative – by US Admiral Joseph Wylie. The results that have come about are as follows – the Israeli armed forces and the state of Israel itself have resorted to a sequential, and Iran and its armed forces to a cumulative strategy. Israel has gradually neutralized or degraded Iran’s partners and allies in order to have a "free hand" for the ultimate operation – the attack on Iran. On the other hand, Iran resorted to missile attacks in response to Israeli aggression whose effects should have had a cumulative effect on Tel Aviv’s position